Governance Dynamics and Financial Risk in Islamic Rural Banks: Assessing the Influence of Board Structures on Financial Performance and Financing Risk - Faridatunnisa , Faridatunnisa; Anwar, Saiful; Rusanti, Ega; Hasbullah, Nornajihah Nadia (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2024)
This study aims to analyze the effects of the board of directors, board of commissioners, Sharia supervisory board, and Non-Performing Financing (NPF) on Return on Assets (ROA) in Islamic rural banks (BPRS) in Indonesia. Additionally, it investigates the influence of the board of directors, board of commissioners, and Sharia supervisory board on NPF. Annual data from 18 BPRS listed in the OJK directory from 2019 to 2021, including board size, ROA, and NPF, were analyzed using the Common Effect Model. The results indicate that board size negatively and significantly affects ROA but not NPF, while board size, board of commissioners, and Sharia supervisory board insignificantly influence ROA and NPF. However, NPF significantly impacts ROA negatively. These results underscore the importance of board composition in financial performance and asset quality within BPRS, providing valuable insights for stakeholders and policymakers in enhancing governance practices and mitigating financial risks